2008
DOI: 10.1038/nnano.2008.318
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes as templates for polymerized lipid assemblies

Abstract: Amphiphilic molecules-molecules that have both hydrophobic and hydrophilic properties-can self-assemble in water to form diverse structures such as micelles, vesicles and tubes, and these nanostructures can be used for delivering drugs, stabilizing membrane proteins or as nanoreactors. We have previously shown that lipids can self-organize on the surface of single-walled carbon nanotubes into regular ring-shaped assemblies. Here we show that these lipid assemblies can be polymerized and isolated from the nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…The cylindrical hollow structure and smooth walls of CNTs provide an excellent opportunity of building nanopumping and nanofiltering devices for water desalination, petroleum filtration, and even kidney dialysis. 210,211 Different methods for transportation of atoms and molecules by CNTs have been introduced by imposing chemical potential and thermal gradients, electrical fields. 32,33,161 Since the relatively low efficiency of the proposed transportation methods, nanopumping effects on the activation of atomic/molecular flows in CNTs by applying mechanical loads were investigated using the propagation of torsional and impulse waves.…”
Section: Application Of Nanoresonator In Molecular Transportationmentioning
confidence: 99%
“…The cylindrical hollow structure and smooth walls of CNTs provide an excellent opportunity of building nanopumping and nanofiltering devices for water desalination, petroleum filtration, and even kidney dialysis. 210,211 Different methods for transportation of atoms and molecules by CNTs have been introduced by imposing chemical potential and thermal gradients, electrical fields. 32,33,161 Since the relatively low efficiency of the proposed transportation methods, nanopumping effects on the activation of atomic/molecular flows in CNTs by applying mechanical loads were investigated using the propagation of torsional and impulse waves.…”
Section: Application Of Nanoresonator In Molecular Transportationmentioning
confidence: 99%
“…[7][8][9][10][11] For example, an edge-in orientation of GO to positively charged lipid layers was reported at the water-air interface; 12 GO was observed to influence the morphology and stability of the supported lipid bilayers; 13 phospholipid monolayer functionalized graphene was demonstrated to have a high loading capacity of cancer drug DOX; and a novel lipid/graphene conjugate was developed as a fluorescence sensor for detection of phospholipase. 14 In this study, CTAB, a commonly used cationic surfactant, was chosen as a model amphiphile.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in our laboratory used PCDA to synthesize the amphiphile 1 (Figure 2) which presents a typical surfactant structure, namely a long hydrophobic chain and a highly polar nitrilotriacetic acid head group. [13] We showed that, on the hydrophobic surface of carbon nanotubes, amphiphile 1 and some other diacetylene amphiphiles can self-assemble into hemi-micellar The effect of photopolymerization on the structure, stability and encapsulation properties of polydiacetylene micelles containing nitrilotriacetic acid head groups are investigated. Micellar nanostructures of 7-10 nm diameter are identified that are invariant after polymerization.…”
Section: Introductionmentioning
confidence: 99%